Pemanfaatan Google Earth Engine untuk Menganalisis Pola Urban Heat Island di Kota Medan - Adelia Putri; Dwi Marsiska Driptufany; Ilham Armi; Dwi Arini; Defwaldi Defwaldi (Jurnal Sains dan Ilmu Terapan, 2025)
Urban Heat Island (UHI) is a climatological phenomenon where urban areas exhibit higher temperatures than their surrounding region due to land use changes and increased built-up areas. Medan, as the third-largest metropolitan city in Indonesia, has experienced rapid population growth, leading to land-use changes and rising surface temperatures. This study aims to map the spatial distribution of UHI in Medan based on Land Surface Temperature (LST) using the Mono Window algorithm on Landsat imagery through Google Earth Engine (GEE) from 2014 to 2023. The results indicate a significant increase in UHI intensity, particularly in highly urbanized areas. Although UHI intensity temporarily decreased in 2017 due to the La Niña phenomenon and haze from forest fires in Sumatra, the overall intensity continued to rise, especially after 2020. In terms of spatial coverage, the Non-UHI area decreased by 630.13 ha, while low, medium, and high-intensity UHI areas increased by 167.41 ha, 437.23 ha, and 26.46 ha, respectively.